Periphytic algal biomass as a bioindicator of phosphorus concentrations in agricultural headwater streams of southern Ontario - Tedeschi AC; Chow-Fraser P (Elsevier, 2021)
Algal blooms in Lake Erie have worsened in recent decades and are driven by diffuse export of phosphorus (P) from a large stream network that drains predominately agricultural land. Given the diffuse nature of nonpoint source pollution, best management practices (BMPs) must target areas where P levels are high. This requires long-term watershed-wide monitoring programs that do not currently exist in many jurisdictions. Instead of conventional nutrient analyses that can be costly and time-consuming, we propose the use of periphyton biomass as a bioindicator of trophic status in low-order streams, where agricultural runoff first enters watercourses. We carried out 2-week in-stream bioassays to measure periphytic algal biomass (CHLperi) in 19 low-order streams in southern Ontario across an agricultural gradient (8 % to 89 %). CHLperi was significantly related to total P (TP) concentration (r2 = 0.46; p = 0.0015) but was not significantly related to soluble reactive P (SRP). A relationship between TP and turbidity (r2 = 0.52; p = 0.0007) is consistent with previous observations of increasing SRP uptake in streams draining agriculturally-dominated landscapes. Stream temperature (°C) was correlated with the proportion of agricultural land (R = 0.55; p = 0.019) and may reflect the warming effects of the sun in unshaded agricultural streams. This method involving substrate rods (Peristix) is cost-effective, requires very little training, and yielded data that were significantly related to TP concentrations in agricultural streams. We recommend that environmental agencies and landowners use this bioassay to identify areas for implementing BMPs to reduce P export from the Lake Erie watershed.
Keywords: 31 Biological Sciences; 3103 Ecology; 15 Life on Land